2022
DOI: 10.3389/fbioe.2022.831545
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of a Low-Invasive Elbow Medial Collateral Ligament Reconstruction Technique With Fascia and Tendon Patches

Abstract: Background: Injury to the medial collateral ligament (MCL) of the elbow has become increasingly common in sports, and the elbow is prone to contracture and ossification in trauma. Effective reconstruction of the MCL with reduction of irritation to the elbow has rarely been reported. This study introduces a minimally invasive elbow MCL reconstruction technique and evaluates the valgus stability.Methods: Eight fresh-frozen elbow specimens underwent reconstruction of the anterior bundle of the MCL (AMCL) first wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In our study, the MCL reconstruction technique consisted of three strips A, B, and C ( Figure 2 ). 21 This new MCL technique is a modification of the previous fascia reconstruction technique. 17 In the new MCL reconstruction technique, we used a longer fascia patch than before, and the fascia patch passed underneath the ulnar carpal flexor and fitted snugly over the bone surface.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our study, the MCL reconstruction technique consisted of three strips A, B, and C ( Figure 2 ). 21 This new MCL technique is a modification of the previous fascia reconstruction technique. 17 In the new MCL reconstruction technique, we used a longer fascia patch than before, and the fascia patch passed underneath the ulnar carpal flexor and fitted snugly over the bone surface.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, biomechanical studies confirmed that the new technique has certain advantages in maintaining elbow valgus stability. 21 Therefore, from the perspective of structural and biomechanical characteristics, we believe that the new technique has an advantage over the traditional technique in maintaining the valgus stability of the elbow.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations